Influence of corners in excavations on damage assessment. Issue 2 (17th September 2018) - Fuentes, Raul
Abstract : This paper provides guidance on quantifying the extent of corner effects in excavations and their impact on damage assessment. The corner effects' extent is of great importance in making early decisions during project planning and preliminary design, particularly in relation to stakeholder engagement and placement of instruments. By using empirical relations, one is able to provide an equation, validated against the literature and additional numerical models, for estimating the extent of corner effects for a particular excavation geometry. Furthermore, two more equations for quantifying the damage of excavations to adjacent structures are presented and validated against two case studies in the literature. The proposed equations are also useful in the context of early stages of project development. Finally, a simple study shows the different effects of corners in sections parallel and perpendicular to a retaining wall. This highlights that corner effects may actually induce additional damage due to the introduction of a movement gradient, as opposed to the common previous perception that assumed that they were always conservative as they reduced absolute movements.